ANALISIS CUSTOMER ENGAGEMENT PADA AKUN MEDIA SOSIAL INSTAGRAM BEDA SEPATUNYA - Adawiyah, Bella Robhiatul; Boer, Kheyene Molekandella (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2023)
The development of the internet and Instagram social media can be utilized as a digital marketing communication strategy. One of the utilization of Instagram social media as a marketing communication medium is to increase customer engagement. One business that also utilizes Instagram social media to increase customer engagement is a shoe laundry service. The purpose of this study is to determine the utilization of Instagram social media in increasing customer engagement of Beda Sepatunya. The type of research used is descriptive research, namely research that makes observations and extracts information. The data sources in this study are primary data and secondary data. The data collection techniques in this research are interviews, observation and documentation. The data analysis technique used in this research is based on the Miles, Huberman, and Saldana interactive model analysis technique, namely data collection, data condensation, data presentation and conclusion drawing. The results of this study indicate that the frequency and consistency of Beda Shoes in managing its Instagram account is still very low, the stage of customer engagement on the Instagram account of Beda Shoes is at the Experiential Engagement stage, namely the customer has shown his involvement with Beda Shoes through Instagram social media but is only limited to liking activities and giving positive comments on Beda Shoes posts. There are still no actions such as posting photos or videos about Beda Shoes.& content exchange are not applied. Some of these models are used to maintain Kahe.id customer engagement.